Characterization of organic and black carbon aerosol formation during coal combustion: An experimental study in a 1 MW pilot scale coal combustor. (15th September 2016) - Wang, Xiaofei; Jing, He; Dhungel, Bhupesh; Wang, Wei-Ning; Kumfer, Benjamin M.; Axelbaum, Richard L.; Biswas, Pratim
Highlights: Emission of carbonaceous aerosols from a pilot-scale coal combustor was studied. Formation of black carbon aerosol was greatly reduced under lower fuel–air ratio. Formation of organic aerosol was slightly enhanced under lower fuel–air ratio. Abstract: Combustion is a main source of atmospheric aerosols, including organic carbon (OC) and black carbon (BC). A pilot-scale coal combustor was used to investigate the formation of organic carbon (OC) and black carbon (BC) aerosols under various combustion conditions. It was found that BC aerosol formation was extremely sensitive to the fuel–oxidizer equivalence ratio: its concentration decreased from 236 μg/m 3 to 2.4 μg/m 3, when the equivalence ratio was reduced from 0.92 to 0.80. However, the emissions of inorganic and OC aerosols were not sensitive to the fuel–oxidizer equivalence ratio. The formation of OC aerosols seemed to be enhanced by decreasing the fuel–oxidizer equivalence ratio, which was opposite to the change of BC aerosol formation. Coal was also combusted in oxygen-rich environments. Inorganic submicrometer particle formation was greatly enhanced in the oxygen-rich combustion mode, compared to conventional air firing. Significant concentrations of OC aerosol were still present in the exhaust gas, while concentrations of black carbon aerosol were under detection limit. The different trends of BC and OC aerosol formation indicate that the formation pathways of OC aerosol are very different from that of BC aerosol formation.